1990
DOI: 10.1007/bf00316801
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic repair/peritoneal toilet of perforated duodenal ulcer

Abstract: Laparoscopic techniques have been refined to the point where exposure, haemostasis and tissue approximation by suture approach those obtained at open access surgery. We report a patient with acute perforation of an ulcer in the first part of the duodenum who was successfully treated by laparoscopic oversewing and omental patching. The clinical indications for contemplating use of laparoscopic surgery for acute ulcer perforation, techniques employed and the areas for potential improvement of instruments, needle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
94
0
5

Year Published

1992
1992
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 177 publications
(101 citation statements)
references
References 1 publication
1
94
0
5
Order By: Relevance
“…Laparoscopic surgery illustrated superior outcomes with respect to less postoperative pain, shorter hospital stays, better comesis, and early recovery [4][5][6][7][8][9][10][11]. Nathanson et al [12] reported the first laparoscopic management of a perforated duodenal ulcer. Since then perforated duodenal ulcers have been managed laparoscopically with ulcer over-sewing and Graham's patch.…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic surgery illustrated superior outcomes with respect to less postoperative pain, shorter hospital stays, better comesis, and early recovery [4][5][6][7][8][9][10][11]. Nathanson et al [12] reported the first laparoscopic management of a perforated duodenal ulcer. Since then perforated duodenal ulcers have been managed laparoscopically with ulcer over-sewing and Graham's patch.…”
Section: Discussionmentioning
confidence: 99%
“…5 The first successful laparoscopic suture repair for perforated peptic ulcer was described by Nathanson et al in 1990. 6 Since then, many studies has been conducted by various authors in different part of world to define the use of laparoscopy in surgical management of perforated peptic ulcer. Costalat et al reported combined endoscopic and laparoscopic approach using ligamentum teres hepatis.…”
Section: Discussionmentioning
confidence: 99%
“…[25] After this approach, many different methods were performed, such as omental patch with fibrin plug, [26] repair with ligamentum teres hepatis, [27] fibrin glue, [7] omental patch application with stapler, [28,29] and fibrin patch (TachoComb). [30] The beneficial effects of fibrin on wound healing have been shown.…”
Section: Discussionmentioning
confidence: 99%